Nutritional status and dietary patterns of stroke survivors under rehabilitation in Terengganu - Ying, C.Y. (2021)
Objective Malnutrition is a major health issue after a stroke which has been linked to poor stroke outcomes, leading to poorer responses to rehabilitation and interfering with recovery. Dietary intake has an impact on rehabilitation recovery but has received little attention. The nutritional status of stroke survivors during the chronic period of the disease is also poorly understood. This study aimed to describe the nutritional status and dietary patterns in stroke survivors under rehabilitation. Methodology A total of 172 stroke survivors under rehabilitation were recruited from the rehabilitation clinic or centre in this cross-sectional study. Nutritional status was assessed using anthropometric indices and dietary patterns were assessed using the Food Frequency Questionnaire (FFQ). The nutritional content was calculated using the Malaysian Food Composition Database. Nutritional status and dietary data were presented descriptively. Results & Discussion The median age of stroke survivors is 60.0,±15.0 years, with 54.7% men and 45.3% women. There were 75.0% of the participants had ischaemic stroke whilst the other 25.0% had haemorrhagic stroke. The median post-stroke duration was 12.0,±23.0 months. The percentages of underweight, normal, overweight, and obese participants were 4.1%, 43.0%, 35.5%, and 17.4%, respectively. Compared to a Mediterranean diet, the stroke participants had demonstrated an unhealthy dietary pattern with a high intake of confectionery (8.6-,±13.8 servings/day), and a low amount of fruits (1.0,±1.6 servings/day) and vegetables (1.2,±1.4 servings/day), and no intake of legumes and nuts. However, the sweetened beverages consumed (0.8-i-±1 .0 drink/day) met the guideline of which less than one drink per day. Conclusion Early detection of malnutrition in stroke survivors, especially in those with poor dietary intake is essential to provide nutritional support to improve rehabilitation outcomes. A dietary modification by emphasising healthy dietary patterns should serve as a guideline in secondary stroke prevention to improve the quality of life of stroke survivors.